Maximum Power Point Tracking Algorithms - Erceg, Tea; Marasovic, Ivan; Betti, Tihomir; Skalic, Ivan (2023 8th International Conference on Smart and Sustainable Technologies (SpliTech), 2023)
This paper presents a comprehensive analysis of the solar cell, covering its equivalent circuit, operating principles, and the effects of temperature and irradiance changes on its current-voltage characteristic. Additionally, the Maximum Power Point Tracking (MPPT) techniques used to determine the maximum current and voltage product under various irradiances are described, and the efficiency of different MPPT techniques is compared to demonstrate the operation of a solar cell. The study also investigates the impact of shading on solar modules by calculating the power loss on two parallel-connected solar panels with different orientations under the same irradiation conditions. The results demonstrate that the Incremental Conductance (IC) algorithm has the best efficiency, followed by Perturb and Observe (P&O) and Hill Climbing (HC) algorithms, under different irradiation conditions. Furthermore, the power loss of the two solar modules with different orientations is significantly affected by the difference in irradiance received by each module. The novelty of this research lies in the comparison of different MPPT techniques under different irradiation conditions and the demonstration of the impact of shading on solar modules with different orientations. This study provides valuable insights for designing and optimizing solar energy systems in real-world conditions, and offers a unique perspective on a well-researched area.